2020
DOI: 10.1093/eurheartj/suaa096
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and atrial tachycardia in patients with chronic thromboembolic pulmonary hypertension treated with pulmonary endarterectomy

Abstract: Atrial fibrillation (AF) and atrial tachycardia (AT) are frequently observed in patients with chronic thromboembolic pulmonary hypertension (CTEPH) who were treated with pulmonary endarterectomy (PEA). Their prevalence and impact on prognosis of patients are not known. We analysed the prevalence of AF/AT and the clinical outcome in 197 patients with CTEPH treated with PEA (median age 62; interquartile range 53–68 years; 62% males). The prevalence of AF/AT was 29% (57 patients). Compared to patients without arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…The prevalence of SVA (18.5%) in our overall PH population was lower than that of two recent studies (29%) 14,15 . Havranek et al 14 analyzed the prevalence of AF/AT in CTEPH patients treated with pulmonary endarterectomy (PEA).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The prevalence of SVA (18.5%) in our overall PH population was lower than that of two recent studies (29%) 14,15 . Havranek et al 14 analyzed the prevalence of AF/AT in CTEPH patients treated with pulmonary endarterectomy (PEA).…”
Section: Discussioncontrasting
confidence: 61%
“…The prevalence of SVA (18.5%) in our overall PH population was lower than that of two recent studies (29%). 14,15 Havranek et al 14 analyzed the prevalence of AF/AT in CTEPH patients treated with pulmonary endarterectomy (PEA). In their study, early post-PEA arrhythmia was also taken into account, which might be the reason of high prevalence of AF/AT.…”
Section: Prevalence Of Arrhythmiasmentioning
confidence: 99%
“…Supraventricular tachycardias (SVT), including atrial fibrillation (AF), have been reported as a common condition in patients with idiopathic pulmonary arterial hypertension (PAH) [3,4] (range of cumulative incidence 10-36%), including all types of PAH [4][5][6][7][8], Eisenmenger's syndrome [9] or inoperable chronic thromboembolic pulmonary hypertension (CTEPH) [4,5,7]. Recently, high prevalence of AF and atrial tachycardia (AT) in CTEPH patients treated with pulmonary endarterectomy was identified with an excessive number of newly diagnosed AF/AT during long-term follow-up after surgery [10]. It has also been demonstrated that SVT in patients with PH frequently lead to clinical deterioration [3][4][5]7,11].…”
Section: Introductionmentioning
confidence: 99%
“…DVT prophylaxis is begun on the evening of surgery and is typically replaced by therapeutic anticoagulation with heparin when the chest tube output is < 50 ml/h for 2 consecutive hours. Atrial arrhythmias occur in about 20-30% of patients postoperatively [83,84].…”
Section: Pulmonary Thromboendarterectomy (Pea)mentioning
confidence: 99%